(untitled) (Journal of the College of Basic Education, 2026)
current research aims to determine the effect of the modified (7ES) strategy on developing practical intelligence among students of the Institute of Fine Arts in the subject of school theater. The researcher adopted the experimental method and the experimental design with two equivalent groups with a pre-test and post-test. The research population included second-year students of the Institute of Fine Arts studying school theater, totaling (254) students. The research sample consisted of (43) students, who were divided into two groups: an experimental group (17) students and a control group (17) students. The researcher used three research instruments: a cognitive achievement test, a skills performance test, and a practical intelligence scale. The psychometric properties of the three instruments were then extracted. After applying the experiment, the results showed the superiority of the students in the experimental group who studied school theater according to the modified (7ES) strategy over the students in the control group who studied school theater according to the traditional method. This indicates the positive effect of the modified (7ES) strategy on the cognitive achievement test, the skills performance test, and the practical intelligence scale. The researcher recommended adopting the (7ES) strategy. The modified 4ES strategy is used in teaching other related subjects at the Institute of Fine Arts.